Pemilihan Kompetensi Keahlian Akuntansi Ditinjau dari Persepsi Peluang Kerja dan Dukungan Orang Tua pada Siswa Kompetensi Keahlian Akuntansi SMK Negeri 6 Surakarta Tahun Ajaran 2014/2015 - Utami, Dewi Tri, Dra. Titik Asmawati, SE., M.Si (2015)
The purpose of this study was to determine: 1) The effect of the perception of employment opportunities for the election of the students' competence of accounting skill competence in State Senior High School 6 Surakarta academic year 2014/2015; 2) The effect of the parental support for the election of the students' competence of accounting skill competence in State Senior High School 6 Surakarta academic year 2014/2015; 3) The effect perception employment of opportunities and the parental support for the selection election of the students' competence of accounting skill competence in State Senior High School 6 Surakarta academic year 2014/2015. This research is descriptive quantitative research with non-experimental research design-survey. The study population is the student student in accounting skills competence state senior high school 6 surakarta academic year 2014/2015 as many as 309 students. Samples taken as many as 161 students with proportional random sampling technique. The technique of collecting data using questionnaires and documentation. Questionnaire previously tested and tested for validity and reliability. Data analysis technique used is multiple linear regression analysis, t test, F test, the coefficient of determination and the relative contribution and effective. Results of regression analysis to obtain the regression line equation: Y = 26.167 + 0,328X1 + 0,300X2. This equation shows that the selection of accounting skills competence is influenced by the perception of employment opportunities and support the parents. The conclusions drawn are: 1) There is a positive influence perceptions of employment opportunities for the students election of accounting skills competence in accounting skills competence state senior high school 6 surakarta academic year 2014/2015. it is based on multiple linear regression analysis (t-test) is known that t count> t table is 5.702> 1.975 and the significance value <0.05 is 0.000 with the effective contribution of 19.35%. 2) There is a positive influence parental support students' for the students election of accounting skills competence in accounting skills competence state senior high school 6 surakarta academic year 2014/2015. It is based on multiple linear regression analysis (t-test) is known that t count> t table is 5.308> 1.975 and the significance value <0.05 is 0.000 with the effective contribution of 17.15%. 3) There is a positive influence on the perception of employment opportunities and support parents together against for the students election of accounting skills competence in accounting skills competence state senior high school 6 surakarta academic year 2014/2015. It is based on analysis of the F test is obtained Fhitung> Ftable is 45.352> 3.06 and a significance value <0.05 is 0.000. The coefficient of determination (R2) of 0.365 indicates that the influence of the perception of employment opportunities and the support of parents is 36.5%, while 63.5% is influenced by other variables not examined.